Equilibrium Kinetic and Thermodynamic Adsorption of Ni and Cd Ions from Waste Water Using Orange Peel - Lina Kareem Amlah; Waleed Muhammed Abood; Dhafer Fezea Ali; Muna Subhi Jamal (Iraqi Journal of Industrial Research)
The aim of this study is to evaluate fresh orange peels as low cost available adsorbent for removing nickel and cadmium ions from laboratory solutions and record the adsorption capacity, which represents the amount of up take per amount of fresh orange peels (FOP). Fourier-Transform Infrared Spectroscopy (FTIR) analyses of FOP was carried out and comparing with the peaks of standard FTIR of cellulose matter to show functional groups and finger print that found in FOP formula. Batch experiments were carried out at different conditions: Ni and Cd ions initial concentration are (10, 20, 30, 40, and 50) ppm, FOP dosage (0.5, 0.75, 1, and 1.5) g, pH (3.5, 5, and 6), contact time (30 to 240) min and temperature (28, 35, and 45) oC where recorded. The results showed that the removal percentage of Ni and Cd increased with increasing FOP dosage. Initial Ni and Cd concentration, pH, and contact time. The best Ni and Cd Removal% where 64% and 80%, respectively at optimum conditions with FOP dosage of 1 g, pH of 6, initial concentration of 50 ppm and contact time of 120 min, where the calculated adsorption capacity was 2.9 mg/g for Ni and 4 mg/g for Cd. In case of the thermal study, best result was obtained at 45 oC with removal% of 65% for Ni and 78% for Cd and adsorption capacity of 2.8 mg/g and 3.7 mg/g for Ni and Cd, respectively.